STRATEGI OPTIMALISASI KEPATUHAN PAJAK MELALUI PENGARUH TARIF PAJAK DAN SANKSI PAJAK: PENDEKATAN SYSTEMATIC LITERATURE REVIEW - Yesi Kumalasari (CV. Denasya Smart Publisher, 2025)
Tax compliance, especially from the MSMEs sector, is one of the important indicators of the success of the self-assessment-based taxation system implemented in Indonesia. However, the level of MSME tax compliance is still relatively low, even in some regions it has not reached 50% of the total business population. This study aims to analyze tax compliance optimization strategies through two main approaches: the influence of tax rates and the effectiveness of tax sanctions. The method used in this study is the Systematic Literature Review (SLR) of journal papers published from 2022-2025. Based on the results of the review of ten empirical studies, it was found that the reduction in tax rates as regulated in PP No. 23 of 2018 tends to increase compliance when supported by an understanding of taxation and simplification of administration. On the other hand, tax sanctions have proven to be effective as a repressive and preventive instrument against tax violations, but only if they are applied consistently and well understood by taxpayers. The disparity in research results shows that the influence of rates and sanctions is not always significant independently, but rather highly dependent on supporting factors such as the quality of tax services, the level of tax literacy, and the effectiveness of policy socialization. A sustainable tax compliance optimization strategy requires synergy between proportional rate reductions, fair application of sanctions, and increasing taxpayer awareness through education and service digitalization. This study recommends a holistic, inclusive, and behavior-based fiscal policy approach to encourage the creation of a stronger compliance culture among MSMEs in Indonesia.